Impact of interdisciplinary interventions on the quality of life of obese people - Obara-Golebiowska, Malgorzata; Salwach-Kuberska, Dominika (Journal of Education, Health and Sport, 2017)
Introduction and the aim of the study: Obesity lowers the health related quality of life of patients. The work was dedicated to analysis of changes in health related quality of life level of obese people participating in organized forms of weight reduction program supported by interdisciplinary team. Material and methods: In the research there were 50 women, age 25 to 65 with body mass index over 30 (obesity rate), abiding Obesity Clinic. There was World Health Organization Quality of Life Test- Bref (WHOQOL- BREF) used in the study. Results: Initial measurement by WHOQOL questionnaire revealed reduced level of general quality of life and health self-assessment of all participants. Subsequent measurement run after two weeks participation in weight reduction program showed substantial result’s improvement in in both variables. Conclusion: In conclusion research presented that participation in organized forms of weight reduction supported by interdisciplinary team consisted of among others psychologist, physician, dietician and physiotherapist results in substantial improvement of patients’ global quality of life and health self-assessment.